Implementation of new hybrid lightweight cryptosystem. Issue 1 (4th May 2018) - Thorat, C.G.; Inamdar, V.S.
Abstract : Embedded systems, Internet of Things (IoT) and mobile computing devices are used in various domains which include public-private infrastructure, industrial installation and critical environment. Generally, information handled by these devices is private and critical. Therefore, it must be appropriately secured from different attacks and hackers. Lightweight cryptography is an aspiring field which investigates the implementation of cryptographic primitives and algorithms for resource constrained devices. In this paper, a new compact hybrid lightweight encryption technique has been proposed. Proposed technique uses the fastest bit permutation instruction PERMS with S-box of PRESENT block cipher for non-linearity. An arbitrary n-bit permutation is performed using PERMS instruction in less than log (n) number of instructions. This new hybrid system has been analyzed for software performance on Advanced RISC Machine (ARM) and Intel processor whereas Cadens tool is used to analyze the hardware performance. The result of the proposed technique is improved by the factor of eight as compared to the PRESENT-GRP hybrid block cipher. Moreover, PERMS instruction bit permutation properties result a very good avalanche effect and compact implementation in the both hardware and software environment.